Targeted multi-platform metabolome analysis and enzyme activity analysis of kiwifruit during postharvest ripening - Mao, Jipeng; Gao, Zhu; Lin, Mengfei; Zhang, Xiaoli; Ning, Xinyi; Gong, Xuchen; Lu, Yupeng; Chen, Lu; Wang, Xiaoling (Frontiers in Plant Science, 2023)
Kiwifruit is a climacteric fruit, in which the accumulation of flavor substances mainly occurs at the postharvest ripening stage. However, the dynamic changes in metabolite composition remain poorly understood. Here, targeted multi-platform metabolome analysis based on GC-MS and UPLC-MS/MS and enzyme activity analysis were performed at different postharvest ripening stages of kiwifruit. A total of 12 soluble sugars and 31 organic acids were identified. The main soluble sugars are sucrose, glucose and fructose, which exhibited similar variation tendencies along with the extension of ripening. The main organic acids are citric acid, quinic acid and malic acid, which showed different variation patterns. A total of 48 energy metabolites were identified, which were classified into two groups based on the content variation. The content of substances related to the respiratory metabolic pathway decreased gradually along with postharvest ripening, and there was obvious accumulation of downstream products such as amino acids at the late ripening stage. A total of 35 endogenous hormones were identified, among which seven cytokinins were highly accumulated at the later stage of softening. We further investigated the dynamic changes in the activities of 28 ripening-related enzymes. As a result, the activities of 13 enzymes were highly correlated with changes in starch, total pectin, and soluble sugars, and those of seven enzymes were closely associated with the change in firmness. In conclusion, this study comprehensively describes the dynamic changes in soluble sugars, organic acids, hormones, energy substances, and ripening-related enzyme activities during kiwifruit postharvest ripening, and provides a theoretical basis for the postharvest quality improvement of kiwifruit.